The role of auditee, auditor, and engagement to audit fee at SOEs - Natalia, Lita; Widarsono, Agus; Widyaningsih, Aristanti (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to analyse the effect of Auditee Aspects, Auditor Aspects and Agreement Aspects, namely Company Size, Company Complexity, Auditor Reputation, and Audit Tenure on Audit Fees in SOES companies in Indonesia. The method in this study is quantitative using a causal associative design. In this study, the sampling technique used purposive sampling, so that 36 SOEs companies from various industrial clusters were obtained for 4 periods (2018-2021). This study uses descriptive statistical analysis and multiple linear regression analysis methods, after passing various classical assumption tests ranging from normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. The results of this study indicate that (1) The auditee aspect as measured using company size has a positive effect on audit fees, while company complexity has no positive effect on audit fees; (2) The auditor aspect as measured by auditor reputation has a positive effect on audit fees and; (3) The engagement aspect, which is measured by audit tenure, has no negative effect on audit fees.